Coca leaf and the national strategy to combat drugs 2007-2011: The public issue in controlling cultivation - Zevallos, Nicolás (Revista de Ciencia Política y Gobierno, 2015)
The National Counternarcotics Strategy 2007,2011 proposed unsuccessfully to reduce the area illegally cultivated of coca leaf in Peru Although the mechanisms of crops control put in place for this purpose met its goals, they brought little to the overall objective This article points out that one of the constraints in this process has been the sub optimization of the public problem underlying the cultivation of coca leaf, so that the mechanisms of crop control fail to meet integrally and homogeneous the interests of farmers who grow coca illegally